A blue can conceal another! Noninvasive multispectroscopic analyses of mixtures of indigo and Prussian blue. Issue 2 (20th December 2019) - Biron, Carole; Mounier, Aurélie; Le Bourdon, Gwénaëlle; Servant, Laurent; Chapoulie, Rémy; Daniel, Floréal
Abstract: Blue colors were sparsely used in the first colored Japanese ukiyo‐e prints but became predominant during the 19th century, mainly due to the integration of the synthetic Prussian blue in the palette of the printers around 1830. For a long time, researchers have assumed that the traditional Japanese organic blue colorants such as indigo were substituted by cheaper Prussian blue. Some analytical studies conducted on such artworks showed evidence of the common use of indigo and Prussian blue in Japanese paintings, alone or mixed together. Recent measurements carried out on bluish areas of an ukiyo‐e designed by Utamaro showed the simultaneous use of the two pigments. However, if visible reflectance spectroscopy suggested the single use of Indigo, Fourier transform infrared spectroscopy (FTIR) also indicated the presence of Prussian blue. These results question about the possible identification of all the pigments of a colored mixture by using a single analytical technique. Without using FTIR spectroscopy, the Prussian blue would not have been detected, whereas on infrared spectra the expected specific bands ascribed to indigo are not identified. The objective of this work is to investigate mixtures of pigments, using noninvasive spectroscopic techniques in order to assess their limits of detection. Fluorimetry, hyperspectral imaging, and infrared spectroscopies have been performed on three color charts made of indigo, Prussian blue, and mixtures of them at different proportions of matter. The results emphasize the systematic identification of Prussian blue thanks to infrared spectroscopy, whereas the identification of indigo, mixed with Prussian blue, appears to be more challenging.